Nocardiopsistins A-C: New angucyclines with anti-MRSA activity isolated from a marine sponge-derived Nocardiopsis sp. HB-J378 - Dongbo Xu; Keshav K. Nepal; Jing Chen; Dedra Harmody; Haining Zhu; Peter J. McCarthy; Amy E. Wright; Guojun Wang (Synthetic and Systems Biotechnology, 2018)
Marine natural products have become an increasingly important source of new drug leads during recent years. In an attempt to identify novel anti-microbial natural products by bioprospecting deep-sea Actinobacteria, three new angucyclines, nocardiopsistins A-C, were isolated from Nocardiopsis sp. strain HB-J378. Notably, the supplementation of the rare earth salt Lanthanum chloride (LaCl3) during fermentation of HB-J378 significantly increased the yield of these angucyclines. The structures of nocardiopsistins A-C were identified by 1D and 2D NMR and HR-MS data. Nocardiopsistins A-C have activity against MRSA (methicillin-resistant Staphylococcus aureus) with MICs of 3.12–12.5 μg/mL; the potency of nocardiopsistin B is similar to that of the positive control, chloramphenicol. Bioinformatic analysis of the draft genome of HB-J378 identified a set of three core genes in a biosynthetic gene cluster that encode a typical aromatic or type II polyketide synthase (PKS) system, including ketoacyl:ACP synthase α-subunit (KSα), β-subunit (KSβ) and acyl carrier protein (ACP). The production of nocardiopsistins A-C was abolished when the three genes were knocked out, indicating their indispensable role in the production of nocardiopsistins. Keywords: Nocardiopsis, Nocardiopsistins, Angucycline, Anti-MRSA, Actinobacteria, LaCl3